The Institutions of Civil Society and Authorities: Cooperation and Ways to Improve - Ivan Aleksandrovich Konnov; Natalia Aleksandrovna Krasilnikova (Управленческое консультирование, 2018)
In the article the questions of legal regulation of interaction of institutions of civil society and authorities at Federal and regional level (on example of the Nizhny Novgorod region), as well as implementation of the requirements of current legislation. The author’s classification of models of interaction between civil society institutions and authorities. Summarizes the problems of interaction between civil society institutions and authorities and the ways of their resolution. The article presents successful practices from the activities of the Legislative Assembly of Nizhny Novgorod region